Determining the implications of the land legislation, 1999 on women's rights to land: A case of Ntendo and Iziya wards in Sumbawanga Urban Council - Sikalumba Alex J; Opiyo Modesta (Mzumbe University, 2026)
The book was sent to DRPS for publications